Effect of Temperature on Microplastic Degradation in Soil Environment - Abah, Moses Adondua; Olawale, Otitoju; Timothy, Mgbede; Timothy, Nwali Chukwuebuka; Oyibo, Okpanachi Nuhu; Okpanachi, Victor; Yola, Anna; Uchechukwu, Ukoh Daniel; Ifeanyi, Onyedinma Emmanuel; Owei, Joy Ebimoboere; Abimbola, Adeyemi Bashirat; Najeeb, Aliyu Olamilekan; Chinenye, Chinweuba Rachael; Egwolo, Fueta Loveth; Iheanacho, Chinedu Christian; Edoka, Oduh Solomon (Asian Journal of Science, Technology, Engineering, and Art, 2024)
The contamination of soil caused by the degradation of plastics introduced through disposal has been increasing globally. Researchers have reported that exposure to microplastics, the degradative product of plastic materials triggers a “wide variety of toxic insults”. The present study aimed at investigating the effect of temperature on microplastic degradation in soil environment. Soil samples were collected from Federal University Wukari farm, air-dried and sieved to obtain fine particles. They were arranged in three groups; one served as the control (Group 1), containing no shredded microplastics, whereas microplastics were shredded in Group 2 and Group 3 soil samples. They were all arranged in triplicates. The control group was kept at room temperature for 14 days whereas Group 2 was exposed to sunlight for 14 days. Group 3 was exposed to sunlight for 7 days. The results obtained from this study revealed the presence of the following microplastic types in Group 2 and 3 soil samples: polyamide, polystyrene, polypropylene, polyethylene, ethylene glycol, terephthatic acid, acrylic acid and polyester. The highest level of total detectable microplastics were associated with Group 3 soil samples (59314.95±808.35), followed by Group 2 soil samples (56022±1352.14) and lastly Group 1 (control) soil samples (32703.51±649.99) respectively. The result also revealed polyamide to be the most abundant microplastic present in all the assayed soil samples: Group 3 (48977.99±1071.61), Group 2 (52204.46±582.03) and Group 1 (28022.08±425.28) whereas the least microplastic present in all assayed soil samples was Terephthatic acid shown as thus: Group 3 (393.69±17.44) > Group 2 (369.36±28.11) > Group 3 (211.32±14.77) respectively. Overall, the result revealed that soil samples exposed to sunlight for a period of 7 days (Group 3) had the highest level of individually detected microplastics followed by soil samples exposed to sunlight for 14 days (Group 2). The control group clearly showed the least levels of individually detected microplastics. The study revealed that microplastics upon exposure to UV rays from sun light could undergo degradation yielding several intermediates which may be either more or less harmful. The study also revealed that the longer the exposure of a microplastic material to UV rays, the higher the degradation rate and the more intermediates associated with the microplastic material will be yielded. On the other hand, the shorter the exposure time of a microplastic material to UV rays, the lesser the degradation rate and less intermediates associated with the microplastic material will be yielded.